Classical and revisionary theism on the divine as personal: a rapprochement? - Burns, Elizabeth (International journal for philosophy of religion, 2015)
To claim that the divine is a person or personal is, according to Swinburne, 'the most elementary claim of theism' ( The coherence of theism, , p. 101). I argue that, whether the classical theist's concept of the divine as a person or personal is construed as an analogy or a metaphor, or a combination of the two, analysis necessitates qualification of that concept such that any differences between the classical theist's concept of the divine as a person or personal and revisionary interpretations of that concept are merely superficial. Thus, either the classical theist has more in common with revisionary theism than he/she might care to admit, or classical theism is a multi-faceted position which encompasses interpretations which some might regard as revisionist. This article also explores and employs the use of a gender-neutral pronoun in talk about God.